Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm working through the first chapter of Michael Spivak's Calculus 3rd ed.

Towards the end of the chapter he proves $ |a + b| ≤ |a| + |b| $ using the observation that $|a|= \sqrt{ a^2 }$ when $a$ is $ ≥ 0 $ .

$ |a + b| ≤ |a| + |b| $

$$ (|a + b|)^2 = (a + b)^2 $$ $$= a^2 + 2ab + b^2 $$ $$ ≤ a^2 + 2|a| |b| + b^2 $$ $$ = |a|^2 + 2|a| |b| + |b|^2 $$ $$ = (|a| + |b|)^2 $$

I am unsure about what's going on with the equality sign. How does it go from $=$ to $≤$ on line 3 when a and b are changed to their absolute value and back to $=$ again on line 4 when $a^2$ and $b^2$ are changed to their absolute values?

share|cite|improve this question
When there is a chain of expressions like this, an = sign only means equal to the immediately preceding line, not to all the previous lines. – Ted Aug 17 '12 at 6:20
Looking at this,I feel you are unable to see why $2|a|*|b| \ge 2ab$.To see why that is being said, just take a=-3 and b=3.That's why the modulus sign is there.Michael Joyce has already posted an answer and as he pointed out , the key is $x\leq |x|$. – user37450 Aug 17 '12 at 6:33
up vote 5 down vote accepted

To extend Ted's comment, Spivak is claiming that: $$a^2 + 2ab + b^2 \leq a^2 + 2|a| |b| + b^2$$ (this follows because $x \leq |x|$ for every $x \in \mathbb{R}$) and that: $$a^2 + 2 |a| |b| + b^2 = |a|^2 + 2 |a| |b| + |b|^2$$ (this follows because $x^2 = |x^2| = |x|^2$ for all $x \in \mathbb{R}$ since $x^2 \geq 0$ for all $x \in \mathbb{R}$).

You can then "string these statements together" to conclude that $$a^2 + 2ab + b^2 \leq |a|^2 + 2 |a| |b| + |b|^2.$$ (The general principle being $x \leq y$ and $y = z$ implies that $x \leq z$.)

Hope that clarifies your confusion.

share|cite|improve this answer
Thanks Michael, that connection makes this proof easier to understand – synk113 Aug 17 '12 at 6:33

Let $a=r_1(\cos A+i\sin A)$ and $b=r_2(\cos B+i\sin B)$

So, $|a|=r_1$ and $|b|=r_2$

Now, $|a+b|=\sqrt{(r_1\cos A + r_2\cos B)^2+(r_1\sin A + r_2\sin B)^2}$


$≤\sqrt{r_1^2+r_2^2+2r_1r_2}\ $ as $\cos(A-B)≤1$ for real A,B


Also observe, $|a+b|=\sqrt{r_1^2+r_2^2+2r_1r_2\cos(A-B)}≥\sqrt{r_1^2+r_2^2-2r_1r_2}=||r_2|-|r_1||$ as $\cos(A-B)≥-1$ for real A,B


share|cite|improve this answer
Perhaps taking $x=a+ib$ and $y=c+id$ would have done the job as well. – user37450 Aug 17 '12 at 6:49

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.